2000
DOI: 10.1592/phco.20.1.105.34662
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mental Status Changes and Hyperchloremic Metabolic Acidosis with Long‐Term Topiramate Therapy

Abstract: Mental status changes and metabolic acidosis may occur with topiramate therapy. These adverse events were reported during dosage titration and with high dosages of the drug. A 20-year-old man receiving topiramate, valproic acid, and phenytoin experienced acute-onset mental status changes with hyperchloremic metabolic acidosis. He had been receiving a modest dose of topiramate for 9 months. He was weaned off topiramate over 5 days, and his mental status returned to baseline within 48 hours of discontinuing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 9 publications
1
45
0
Order By: Relevance
“…This includes anorexia or paresthesia, whereas the chronic condition is associated with increased risk for kidney stones, osteomalacia, or osteoporosis. [1][2][3][4]8 Occurrence of lower bicarbonate levels in patients taking TPM has been described in several case reports [10][11][12][13] and some clinical studies. 6,[15][16][17] However, no significant correlation was observed previously between the length of TPM therapy and bicarbonate or potassium levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes anorexia or paresthesia, whereas the chronic condition is associated with increased risk for kidney stones, osteomalacia, or osteoporosis. [1][2][3][4]8 Occurrence of lower bicarbonate levels in patients taking TPM has been described in several case reports [10][11][12][13] and some clinical studies. 6,[15][16][17] However, no significant correlation was observed previously between the length of TPM therapy and bicarbonate or potassium levels.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,8,9 Several case reports have indicated that TPM can cause metabolic acidosis in patients. [10][11][12][13][14] Also, a number of clinical trials have shown that TPM decreases serum bicarbonate levels. 6,[15][16][17] Metabolic acidosis was previously observed in 48% of patients treated with TPM in a retrospective cohort study.…”
Section: Background and Objectivementioning
confidence: 99%
“…The most common side-effects are not dose related and usually involve the central nervous system [2]. Metabolic acidosis has been reported after topiramate overdose, in children and during longterm therapy [3]. The early metabolic adverse effect of topiramate in our case suggests that the acidosis may be an idiosyncratic reaction or related to the rapid increment in dose.…”
Section: Topiramate Induced Metabolic Acidosismentioning
confidence: 64%
“…), this is a well documented adverse event induced by TPM [2][3][4][5] . Metabolic acidosis is probably due to the carbonic anhydrase inhibitory effect of TPM, which increases the bicarbonate lost in the urine, and consequently, decreases CO 2 serum levels 2 .…”
Section: Resul Resul Resul Resul Results Ts Ts Ts Tsmentioning
confidence: 97%